Perancangan Aplikasi Parenting Dalam Pemberian Tugas dan Reward Untuk Anak - Aulia Rahmawati; Kiki Reski Ramdhani S. (Prodi Sistem Informasi UIN Alauddin, 2022)
The role of parents in raising children is very influential for the growth and development of children, how parents form habits and build character and mindset in children. Even in the process, it will not always run smoothly and well, parents must always try and innovate in attracting children's interest so that children feel challenged and happy with carrying out the tasks given. As for the application made for parents in educating children, not only that the Wase application can also be used to build children's skills, and participate in child care in everyday life. In order to increase the enthusiasm of children in carrying out the tasks written in the task column and then the results will get rewards in the form of points that can be used to claim bigger rewards. With this application as a media for parents to do fun parenting and motivate daily activities set by parents on tasks, it can form good habits and is expected to be useful and increase children's motivation in forming good daily habits.